Dexmedetomidine Inhibits Inflammatory Reaction in Lung Tissues of Septic Rats by Suppressing TLR4/NF-κB Pathway - Yuqing Wu; Yingchun Liu; He Huang; Yangzi Zhu; Yong Zhang; Fuzhao Lu; Ce Zhou; Li Huang; Xin Li; Chenghua Zhou (Hindawi Limited, 2013)
Dexmedetomidine has been reported to reduce mortality in septic rats. This study was designed to investigate the effects of dexmedetomidine on inflammatory reaction in lung tissues of septic rats induced by CLP. After induction of sepsis, the rats were treated with normal saline or dexmedetomidine (5, 10, or 20 μg/kg). The survival rate of septic rats in 24 h was recorded. The inflammation of lung tissues was evaluated by HE stain. The concentrations of IL-6 and TNF-α in BALF and plasma were measured by ELISA. The expressions of TLR4 and MyD88 were measured by western blotting. The activation of NF-κB in rat lung tissues was assessed by western blotting and immunohistochemistry. It was found that the mortality rate and pulmonary inflammation were significantly increased in septic rats. IL-6 and TNF-α levels in BALF and plasma, NF-κB activity, and TLR4/MyD88 expression in rat lung tissues were markedly enhanced after CLP. Dexmedetomidine (10 and 20 μg/kg) significantly decreased mortality and pulmonary inflammation of septic rats, as well as suppressed CLP-induced elevation of TNF-α and IL-6 and inhibited TLR4/MyD88 expression and NF-κB activation. These results suggest that dexmedetomidine may decrease mortality and inhibit inflammatory reaction in lung tissues of septic rats by suppressing TLR4/MyD88/NF-κB pathway.